Uso de disilicato de litio y zirconia en rehabilitación oral. - Castillo Paredes, Fabricio Paul (2024)
The current research entitled “Use of Lithium Disilicate and Zirconia in Oral Rehabilitation.” It aimed to establish the clinical uses of these two types of restorative materials. Both lithium disilicate and zirconia are widely used in the field of oral rehabilitation. The research was done through a systematic literature review, compiling the most relevant information from critical scientific databases such as PubMed, Science Direct, and Wiley. The researcher selected and collected scientific articles using the PICOS methodology, considering the impact indicators Scimago Journal Ranking and Average Count Citation. Choosing articles mentioning the mechanical properties and clinical indications of lithium disilicate and zirconia was essential. Consequently, the researcher obtained 53 scientific articles. The results of scientific publications show that lithium disilicate has a high flexural resistance due to the intertwined microstructure of the crystals that act as a hardening mechanism against the expansion of cracks. This material satisfies the aesthetic and mechanical aspects by providing optimal translucency. It has physical characteristics similar to natural teeth. It is less brittle and rigid and causes less wear on natural teeth. Zirconia has suitable properties such as high fracture toughness. It is highly resistant to flexure, corrosion, and wear; thermal conductivity is low; adequate biocompatibility, greater affinity with bone tissue, and low affinity with bacterial plaque. In conclusion, the choice between the two types of ceramics will depend on the specific clinical requirements, such as the location of the restoration, the desired esthetics, strength considerations, and functional demands.